The effectiveness of water spinach (Ipomoea aquatica) as a phytoremediator of leachate from Banyuroto landfill - Widakdo, Widakdo; Suhartini, Suhartini (Universitas Negeri Yogyakarta, 2025)
Water spinach (Ipomoea aquatica) possesses hyperaccumulator properties, a high level of tolerance, and fast growth. These characteristics indicate that water kale (Ipomoea aquatica) can remediate leachate which is a source of pollution around the Banyuroto landfill. This study aims to (1) evaluate the effectiveness of the water spinach plant (Ipomoea aquatica) as a phytoremediator for Banyuroto landfill leachate, (2) assess the plant's performance as a phytoremediator for Banyuroto landfill leachate. A single factor Completely Randomized Design (CRD) was used with Leachate concentration treatments of 10%, 20%, 30%. Observed parameters included leachate water quality (BOD, COD, TSS, pH, total N, cadmium) and plant performance (number of leaves and wet weight). Leachate water quality was analyzed using the effectiveness calculation, while plant performance was carried out using One Way Anova. The results showed the highest effectiveness of phytoremediation at the 10% level for BOD, COD, TSS parameters. The highest total effectiveness parameter N is at the 20% level. Cadmium parameters at all levels of effectiveness value are the same. Furtehrmore, leachate had no significant effect on the growth performance of water spinach.